Student Career Planning Through Group Guidance Services - Nisya, Wirdatun; Firman, Firman; Netrawati, Netrawati (Universitas Trunojoyo Madura, 2023)
Career planning for students is important to optimize by providing the best stimulation. One of the stimulations that can be done by counseling teachers is by providing group guidance services. The purpose of this study was to find out how the role of group guidance services in improving career planning in students. The method used in this research is the library research method. The way of collecting data in this study is by using the documentation method and collecting written sources related to career planning using group guidance services. The results of this study explained that group guidance services can improve career planning in students. This article has implications for encouraging counseling teachers to use the group counseling service method to introduce career planning to students.